Chloride ion storage performance of polyaniline/graphene nanocomposite in aqueous sodium chloride solution. (June 2021) - Zhu, Tiantian; Kong, Hui; Xia, Tianchen; Shen, Yuyin; Miao, Yingchun; Zhao, Xiangyu
Graphical abstract: Highlights: The polyaniline/graphene material is first employed as the faradaic electrode in the desalination system. The as-prepared polyaniline-based electrode delivers a high reversible capacity of 126 mA h g −1 . Competitive chloride ion storage performance of the polyaniline electrode is achieved. Abstract: The use of anion storage materials has played an important role in the development of electrochemical energy storage systems and water desalination. Herein, the graphene-supported polyaniline (PANI/GN) nanomaterial is developed as a new chloride ion storage electrode in aqueous sodium chloride solution. The as-prepared PANI/GN electrode exhibits highly reversible electrochemical stability in both a three-electrode system and a full desalination battery using a sodium ion storage electrode. Competitive electrochemical properties with a reversible capacity of 126 mA h g −1, a coulombic efficiency of more than 95 % and a high rate capability are achieved for the PANI/GN electrode compared to the previously reported electrodes of metals, antimony oxychloride, and polypyrrole. The anionic chloride species instead of covalent chloride species in the as-prepared PANI/GN is demonstrated to be electrochemically active.